PENGARUH BADAN USAHA MILIK DESA MITRA JAYA MANDIRI UNIT SIMPAN PINJAM TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DESA BANGUN JAYA KECAMATAN TAMBUSAI - Husri (Jurnal Ilmiah Cano Ekonomos, 2023)
This study aims to investigate the influence of BUMDES Mitra Jaya Mandiri Savings and Loans units on the level of community welfare. The research method is a descriptive survey of 400 BUMDes members of the saving and loan unit. Sampling used purposive random sampling technique, so the number of samples was 200. Data analysis used SPSS 24. The research findings revealed that BUMDes saving and loan activities had an overall positive effect on various indicators of community welfare.